Statistical evaluation of landfill leachate system and its impact on groundwater and surface water in Malaysia - Tawfiq J.H. Banch,; Marlia M. Hanafiah,; Alkarkhi, Abbas F.M.; Abu Amr, Salem S. (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this study, leachate collection and processing system in Ampar Tenang Closed Landfill (ATCL) and its impact on both groundwater and surface water was evaluated. Samples from three locations in leachate processing system (Collection, aeration and stabilization ponds), groundwater and surface water were collected and tested for twenty-one parameters covering nine heavy metals (Fe2+, Zn2+, Cu2+, Cr2+, Cd2+, Pb+, As3+, Co2+ and Mn2+) and twelve physiochemical parameters (Mg2+, Ca2+, Na+, chemical oxygen demand (COD), biochemical oxygen demand (BOD), total dissolved solids (TDS), total suspended solids (TSS), electrical conductivity (EC), pH, ammoniacal nitrogen (NH3-N) and dissolved oxygen (DO). Correlation analysis for landfill leachate ponds, groundwater and surface water showed different patterns of relationships between all possible combinations of two parameters. Similarity and dissimilarity were studied through cluster analysis, three clusters were found to entirely separate the collection pond (cluster 1) while the two ponds were clustered with groundwater samples (cluster 2) and the third cluster is for the surface water. This study shows the benefit of statistical analysis such as correlation analysis and cluster analysis for evaluation and interpretation of landfill data to understand the behavior of the selected parameters and to have a clear picture about the pattern of the relationship for effective landfill management.